Evaluating Medium Chain Fatty Acids as an Alternative to Chlortetracycline in Nursery Pig Diets - R. A. Cochrane; J. R. Pluske; J. P. Mansfield; S. S. Dritz; J. C. Woodworth; M. D. Tokach; M. C. Niederwerder; C. B. Paulk; C. K. Jones (Kansas Agricultural Experiment Station Research Reports, 2018)
An experiment was conducted to evaluate medium chain fatty acids (MCFA) as a potential alternative to chlortetracycline (CTC) in nursery pigs. One hundred entire male pigs (initially 14.1 ± 1.6 lb body weight (BW) and weaned at 22 d of age) were used in a 29-d disease challenge study. Pigs were allowed 5 acclimation days after weaning, followed by 2 d of disease challenge with Enterotoxigenic β-hemolyticEscherichia coli(ETEC), serotype O149:K91: K88. After the challenge, pigs were allotted to a diet with 1 of 5 treatments: 1) control with no additives; 2) 400 g/ton CTC (Chlortet 200G, Eco Animal Health, London, United Kingdom); 3) 1.08% of a 1:1:1 blend of C6:0, C8:0, and C10:0 (Nuscience Group, Drongen, Belgium); 4) 3.93% developmental Product A (Nuscience Group, Drongen, Belgium); and 5) 1.04% developmental Product B (Kemin Industries, Des Moines, IA, USA). Treatments 3, 4, and 5 were included at rates to derive a 1% MCFA concentration in finished feed. Pigs were fed treatment diets for 14 days following the disease challenge to mimic a therapeutic dose of CTC and fed a common diet from d 14 to 21. There was no evidence of difference (P>0.10) of dietary treatment on growth performance from d 0 to 7 or d 14 to 21. From d 7 to 14, pigs fed diets with added CTC, 1:1:1 blend, or Product B had improved (P<0.05) F:G compared to those fed the control diet, with pigs fed diets with Product A intermediate. A treatment × day interaction for the ETEC fecal shedding was observed (P<0.05), which was driven by pigs fed diets with CTC having decreased (P<0.05) fecal shedding on d 7 than d 14, while those fed diets with Product B having greater (P<0.05) fecal ETEC shedding on d 1 than d 14. While other disease markers, such as fecal score, plasma urea nitrogen, and haptoglobin, decreased (P<0.05) with time, they were not affected (P>0.05) by dietary treatment. In conclusion, supplementing ETECchallenged nursery pigs with MCFA-based dietary treatments led to similar growth performance as a therapeutic dose of 400 g/ton of CTC. Further research is needed to confirm the mode of action, most effective MCFA or combination, and effective dose of medium chain fatty acids in ETEC-challenged pigs.
Keywords: chlortetracycline; Enterotoxigenic Escherichia coli; medium chain fatty acids; pig